2000
DOI: 10.1080/00016480050218744
|View full text |Cite
|
Sign up to set email alerts
|

Pain Treatment after Tonsillectomy: Advantages of Analgesics Regularly Given Compared with Analgesics on Demand

Abstract: The aim of the present prospective study was to evaluate pain treatment during the first postoperative 24 h for 40 patients (age over 18) undergoing tonsillectomy. Patients were divided into two groups: group A (n = 20) received analgesics on demand and group B (n = 20) on a regular basis. Basic pain treatment consisted of paracetamol 750 mg x 6 and diclofenac 50 mg x 3. Pain measurement was performed using a visual analogue scale (VAS): a 10 cm line with 0 cm equalling no pain and 10 cm equalling the worst pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
2

Year Published

2002
2002
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 14 publications
0
4
0
2
Order By: Relevance
“…This is in agreement with the generally held expectation that older people have more pain after tonsil surgery than children. We followed a regime based on results reported by Thorneman and Åkervall, 12 who showed that a regular postoperative schedule for pain treatment after TE has advantages compared with taking analgesics only on demand.…”
Section: Discussionmentioning
confidence: 99%
“…This is in agreement with the generally held expectation that older people have more pain after tonsil surgery than children. We followed a regime based on results reported by Thorneman and Åkervall, 12 who showed that a regular postoperative schedule for pain treatment after TE has advantages compared with taking analgesics only on demand.…”
Section: Discussionmentioning
confidence: 99%
“…Only two trials so far have compared regular versus rescue analgesia following tonsillectomy, and the results are conflicting. The earlier trial (non-randomized controlled) found regular analgesia to be more efficacious (better pain control and earlier return to solid feeds), 28 whereas a more recent (randomized controlled) trial found no significant benefit with a regular regimen. 29…”
Section: Additional Adjuvantsmentioning
confidence: 95%
“…Recently NSAIDS have been shown to be effective in regulating pain after tonsillectomy. Regularly given postoperative pain treatment after tonsillectomy, starting intraoperatively, has shown significant advantages compared with a regimen on demand [26]. Compared with opioids, ( NSAIDs were found to be equianalgesic and the risk of emesis was significantly decreased [27].…”
Section: A Non-steroidal Anti-inflammatory Drugs (Nsaids)mentioning
confidence: 99%